Integrating Multiple Perspectives Into the Study of Resilience. Issue 2 (4th July 2016) - January, Samantha C.
Abstract : Resilience has become a popular buzzword in society today, both inside and outside academia. If you look at the mission statement of most companies nowadays, you are likely to come across some form of the term resilience. The United States Army has adopted The Ready and Resilient Campaign, which seeks to build and maintain resilience across all forces and integrate resilience into the culture of the U.S. Army so that improvements can be made in soldier resilience and unit readiness.